Incidence and characteristics of eravacycline-associated increase in serum bilirubin levels: a retrospective study - Si, Yueyue; Chen, Man; Zhang, Jicheng; Jiang, Jinjiao; Zhang, Yahui; Yu, Guofeng; Guo, Nan; Yan, Genquan; Leng, Bing (Frontiers in Pharmacology, 2026)
ObjectivesTo compare the effects of eravacycline and tigecycline on serum bilirubin levels and investigate the incidence and clinical characteristics of total bilirubin increase associated with eravacycline.MethodsWe conducted a retrospective study in critically ill patients receiving eravacycline or tigecycline between November 2023 and May 2024 to evaluate serum bilirubin levels. Causality was assessed using the Naranjo Adverse Drug Reaction Probability Scale. A multivariable logistic regression was conducted to identify the risk factors for an increase in total bilirubin, and Kaplan-Meier curves were used to depict the time to an increase in total bilirubin.ResultsA total of 48 patients were evaluated in this study. Compared to tigecycline, eravacycline was associated with elevated serum total bilirubin and direct bilirubin. Following the definition of an increase in total bilirubin levels as ≥42 μmol/L, 15 patients were rated as possibly or probably having drug-associated increase in total bilirubin. The incidence of an increase in total bilirubin was 61.5% in the eravacycline group and only 20.0% in the tigecycline group. Administration of eravacycline was identified as an independent risk factor for an increase in total bilirubin. In addition, patients receiving eravacycline tended to experience an increase in total bilirubin significantly earlier, and the change in direct bilirubin levels was significantly greater than that in indirect bilirubin in these patients.ConclusionEravacycline has been identified as an independent risk factor for the increase in total bilirubin. Monitoring serum bilirubin levels should be considered in patients receiving eravacycline, particularly in critically ill patients.